Fishing Cooperative and their Endogenous Touristic Strengths as a Local Development Option - Jacquez, Maria Estela Torres (Anais Brasileiros de Estudos Turísticos, 2015)
The fishing cooperative organizations seek to become the revenues to improve the living standards of those involved and their populations. However, periods of capture, comprising about six months a year, the other month’s fishermen engaged in alternative activities to fishing, on the other hand when these possess endogenous strengths that can be leveraged through the exploitation of ecotourism and influence in local development. This document is part of a broader investigation aimed at identifying tourism resources of fishing cooperatives as an endogenous factor for local development. The research is qualitative and techniques used to obtain information were semi-structured interviews with partners and managers of fishing cooperatives, along with observation. Empirical evidence shows that fishing cooperatives, without professional training, perform the tourist services in the estuaries through boat tours where appreciates the diverse flora such as mangroves, endemic and migratory bird watching, and fishing, among others. Therefore, we conclude that cooperatives develop alternative tourism activities generating additional revenue for community development, but their services are limited because they do empirically.